A Comprehensive Review on Rasam: A South Indian Traditional Functional Food - Devarajan, Agilandeswari; Mohanmarugaraja, M. K. (Pharmacognosy Reviews)
The view that food can have an expanded role that goes well beyond providing a source of nutrients truly applies to traditional functional foods. The systematic consumption of such traditional functional food provides an excellent preventive measure to ward off many diseases. Rasam, a soup of spices, is a traditional South Indian food. It is traditionally prepared using tamarind juice as a base, with the addition of Indian sesame oil, turmeric, tomato, chili pepper, pepper, garlic, cumin, curry leaves, mustard, coriander, asafoetida, sea salt, and water. Rasam is a classic example of traditional functional food with all its ingredients medicinally claimed for various ailments. The preclinical and clinical studies on rasam and its ingredients support their traditional claim. This review is an attempt to compile the literatures on rasam, its ingredients, and to highlight its medicinal potential that has been underestimated.
Keywords: Asafoetida; black pepper; garlic; preventive medicine; spice soup; turmeric